Beiträge zum Göttinger Umwelthistorischen Kolloquium 2004 2006 - Herrmann, Bernd (f3104510-575d-4f7c-b004-e0e499c2fe4a, 2007)
Ever since its establishment 25 years ago the 'Göttingen Environmental Colloquium' has developed into an institution that bundles the various activities on the subject here and from all other areas in the German-speaking countries by exchanging the results of research and the various streams of scientific endeavours in ths field. Also some start-up enterprises have originated here. The volume assembles papers of the 2004 to 2006 colloquia. During those years the GEC extended its scope through cooperation with the Göttingen Graduate College "Interdisciplinary Environmental History". The papers ideally present the idea of interrelated departmental research into environmental history, both in their thematic approach and according to the specialized competence of the authors.